THE NON-CONTRACTUAL LIABILITY OF THE EU – CASE STUDY OF ŠUMELJ CASE - Petrašević, Tunjica; Krmek, Mato (EU and comparative law issues and challenges series (ECLIC), 2018)
The EU is in obligation to cover the damage to member states and individuals on behalf of the institution that caused it. There is contractual and non-contractual liability of the EU. The aim of this paper is to discuss the non-contractual liability of the EU with special reference to joint liability of the EU and member states. In that sense, we will discuss the case “Šumelj and Others v Commission”, which is the first Croatian case before the Court of Justice of the European Union (CJEU). The action was brought before the General Court on 20 October 2013. The applicants claimed that the Commission had breached its obligation to monitor the implementation of the Treaty concerning the accession of the Republic of Croatia to the European Union, under Article 36 to the Act of Accession. The General Court recently issued a negative decision. The applicants lodged an appeal to the Court of Justice but the Court confirmed General Court’s decision So, we analyse the judgment of the General Court.